Endoscopic and keyhole endoscope-assisted neurosurgical approaches: a qualitative survey on technical challenges and technological solutions - Marcus,HJ; Cundy,TP; Hughes-Hallett,A; Yang,GZ; Darzi,A; Nandi,D (British Journal of Neurosurgery, 2014)
The literature reflects a resurgence of interest in endoscopic and keyhole endoscope-assisted neurosurgical approaches as alternatives to conventional microsurgical approaches in carefully selected cases. The aim of this study was to assess the technical challenges of neuroendoscopy, and the scope for technological innovations to overcome these barriers. Materials and methods. All full members of the Society of British Neurosurgeons (SBNS) were electronically invited to participate in an online survey. The open-ended structured survey asked three questions; firstly, whether the surgeon presently utilises or has experience with endoscopic or endoscope-assisted approaches; secondly, what they consider to be the major technical barriers to adopting such approaches; and thirdly, what technological advances they foresee improving safety and efficacy in the field. Responses were subjected to a qualitative research method of multi-rater emergent theme analysis. Results. Three clear themes emerged: 1) surgical approach and better integration with image-guidance systems (20%), 2) intra-operative visualisation and improvements in neuroendoscopy (49%), and 3) surgical manipulation and improvements in instruments (74%). Discussion. The analysis of responses to our open-ended survey revealed that although opinion was varied three major themes could be identified. Emerging technological advances such as augmented reality, high-definition stereo-endoscopy, and robotic joint-wristed instruments may help overcome the technical difficulties associated with neuroendoscopic approaches. Conclusions. Results of this qualitative survey provide consensus amongst the technology end-user community such that unambiguous goals and priorities may be defined. Systems integrating these advances could improve the safety and efficacy of endoscopic and endoscope-assisted neurosurgical approaches.